Dimethylarginine dimethylaminohydrolase (DDAH) overexpression enhances wound repair in airway epithelial cells exposed to agricultural organic dust. (23rd February 2018) - Chandra, Deepak; Poole, Jill A.; Bailey, Kristina L.; Staab, Elizabeth; Sweeter, Jenea M.; DeVasure, Jane M.; Romberger, Debra J.; Wyatt, Todd A.
Abstract: Objective: Workers exposed to dusts from concentrated animal feeding operations have a high prevalence of pulmonary diseases. These exposures lead to chronic inflammation and aberrant airway remodeling. Previous work shows that activating cAMP-dependent protein kinase (PKA) enhances airway epithelial wound repair while activating protein kinase C (PKC) inhibits wound repair. Hog barn dust extracts slow cell migration and wound repair via a PKC-dependent mechanism. Further, blocking nitric oxide (NO) production in bronchial epithelial cells prevents PKA activation. We hypothesized that blocking an endogenous NO inhibitor, asymmetric dimethylarginine, by overexpressing dimethylarginine dimethylaminohydrolase mitigates the effects of hog dust extract on airway epithelial would repair. Materials/methods: We cultured primary tracheal epithelial cells in monolayers from both wild-type (WT) and dimethylarginine dimethylaminohydrolase overexpressing C57Bl/6 (DDAH1 transgenic) mice and measured wound repair using the electric cell impedance sensing system. Results: Wound closure in epithelial cells from WT mice occurred within 24 h in vitro . In contrast, treatment of the WT cell monolayers with 5% hog dust extract prevented significant NO-stimulated wound closure. In cells from DDAH1 transgenic mice, control wounds were repaired up to 8 h earlier than seen in WT mice. A significant enhancement of wound repair was observed in DDAH cells compared to WT cells treated with hog dust extract for 24 h. Likewise, cells from DDAH1 transgenic mice demonstrated increased NO and PKA activity and decreased hog dust extract-stimulated PKC. Discussion/conclusion: Preserving the NO signal through endogenous inhibition of asymmetric dimethylarginine enhances wound repair even in the presence of dust exposure.